2002
DOI: 10.1128/iai.70.7.3953-3958.2002
|View full text |Cite
|
Sign up to set email alerts
|

Analogous Cytokine Responses toBurkholderia pseudomalleiStrains Contrasting in Virulence Correlate with Partial Cross-Protection in Immunized Mice

Abstract: Cytokine mRNA levels were assessed in Burkholderia pseudomallei-susceptible BALB/c mice and B. pseudomallei-resistant C57BL/6 mice following administration of a sublethal dose of less virulent (LV) B. pseudomallei, a candidate immunogen tested for protection against a highly virulent (HV) challenge. Compared on the basis of the bacterial loads, the cytokine patterns induced by HV and LV B. pseudomallei were similar, involving gamma interferon, interleukin-10, and other cytokines. Partial cross-protection betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 36 publications
4
15
0
Order By: Relevance
“…However, it is possible that latent infection, not detectable by standard culture techniques, resulting from immunization with CL04 might reappear subsequently considering the extremely chronic recrudescent nature of melioidosis. The current observations are consistent with previously reported clearance rates for less virulent B. pseudomallei [15] and, combined with the comparative immunization data in this study illustrates unique immunogenicity traits amongst B. pseudomallei isolates even where individual strains are equivalent in virulence and in clearance kinetics in mice. Immunogenicity of B. pseudomallei isolates therefore appears to be associated with specific bacterial components present in particular strains.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, it is possible that latent infection, not detectable by standard culture techniques, resulting from immunization with CL04 might reappear subsequently considering the extremely chronic recrudescent nature of melioidosis. The current observations are consistent with previously reported clearance rates for less virulent B. pseudomallei [15] and, combined with the comparative immunization data in this study illustrates unique immunogenicity traits amongst B. pseudomallei isolates even where individual strains are equivalent in virulence and in clearance kinetics in mice. Immunogenicity of B. pseudomallei isolates therefore appears to be associated with specific bacterial components present in particular strains.…”
Section: Discussionsupporting
confidence: 94%
“…Immunization-induced immunity could not protect mice from higher LC doses. Moreover, considerable bacterial loads at several weeks after LC in immunized mice illustrates non-sterilizing immunity, which is consistent with a previous study [15]. Gene microarray assessment of mRNA expression identified several unique immunization-associated genes including GM-CSF, Bad and TERT/TP2 in BALB/c mice and CDK5 in C57BL/6 mice.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…; however, these were insufficient to inhibit the hyperproduction of proinflammatory responses in the lungs, NALT, and OM. Interestingly, the levels of many cytokines in the lungs, NALT, and OM were not proportionate to the B. pseudomallei colonization load in the tissue; similar results were reported for the spleen (66).…”
Section: Discussionsupporting
confidence: 68%
“…However, in BALB/c mice, the level of expression of some of these cytokines including IFN-␥ was greater than in C57BL/6 mice, which was interpreted as a possible role for endotoxic shock and a cytokine-mediated immunopathology in the development of melioidosis [39]. It was further found that the mixed Th1-and Th2-like cytokine response induced by highly virulent and less virulent strains of B. pseudomallei, correlated with partial cross-protection between the two strains in mice previously immunized with the less virulent B. pseudomallei candidate vaccine strain [40].…”
Section: Discussionmentioning
confidence: 77%